Convolutional Neural Networks in the Detection of Astronomical Objects from the Messier Catalog - Beluch, Witold; Śliwa, Paweł (Computer Assisted Methods in Engineering and Science; Vol 30 No 4 (2023), 2023)
This paper explores the application of convolutional neural networks in the field of amateur astronomy. The authors have employed the available astronomical datasets to develop a detector for identifying astronomical objects from the Messier catalog. A concept framework for creating such a detector for astronomical objects using artificial intelligence tools in the form of a detector based on convolutional neural networks is presented. Augmentation and pre-processing procedures have been used to extend the feature distribution in the training set. Examples confirming the effectiveness of the proposed detector of astronomical objects are presented.